Utilisation of performance markers to establish the effectiveness of cold-water immersion as a recovery modality in elite football. - Jill Alexander; Chris Carling; David Rhodes (Termedia Publishing House, 2021)
Optimal strategies for recovery following training and competition in elite athletes presents ongoing debate. The effects of cold-water immersion (CWI) compared to passive recovery (PR) though a triad of performance measures after fatiguing exercise within a normal micro-cycle, during mid-competitive training cycle, in elite male footballers were investigated. Twenty-four elite footballers (age 20.58 ± 2.55 years; height 179.9 ± 5.6 cm; weight 75.7 ± 7.5 kg; body fat 6.2 ± 1.7%) were randomly assigned to CWI or PR following a fatiguing training session. Objective measures included eccentric hamstring strength, isometric adductor strength, hamstring flexibility and skin surface temperature (Tsk). Subjective measures included overall wellbeing. Data were collected at match day+3, immediately post-training, immediately post-intervention and 24 hrs post-intervention. Physiological, biomechanical and psychological measures displayed significant main effects for timepoint for eccentric hamstring strength, Tsk, overall wellbeing, sleep, fatigue, stress and group for eccentric hamstring strength, Tsk and sleep (groups combined). Group responses identified significant effects for timepoint for CWI and PR, for eccentric hamstring strength peak force, sleep, fatigue, and muscle soreness for CWI. Significant differences were displayed for eccentric hamstring strength (immediately post-intervention and immediately post-training) for peak force and between CWI and PR eccentric hamstring strength immediately post-intervention. Linear regression for individual analysis demonstrated greater recovery in peak torque and force for CWI. CWI may be useful to ameliorate potential deficits in eccentric hamstring strength that optimise readiness to train/play in elite football settings. Multiple measures and individual analysis of recovery responses provides sports medicine and performance practitioners with direction on the application of modified approaches to recovery strategies, within mid-competitive season training cycles.